PENGARUH ORIENTASI KEWIRAUSAHAAN, RELIGIUSITAS DENGAN LITERASI KEUANGAN SEBAGAI VARIABEL MODERASI TERHADAP KINERJA UMKM KABUPATEN KUDUS - Indah Puspita Maharani; Diah Ayu Susanti; Ahmad Nilnal Munachifdlil ‘Ula (Jurnal Manajemen Bisnis Krisnadwipayana, 2024)
This research aims to determine the influence of entrepreneurial orientation, religiosity on the performance of MSMEs with financial literacy as a moderating variable. The object of this research is MSMEs in Kudus district. The research method used is a quantitative method with data analysis techniques using PLS-SEM. The sampling technique in this research used a purposive sampling method and the data collection method used questionnaire distribution. The research results show that entrepreneurial orientation has a positive effect on MSME performance, while religiosity has no effect on MSME performance. On the other hand, the role of financial literacy in moderating the influence of company orientation and religiosity on MSME performance is not proven. It is hoped that these results will provide insight for MSME actors about how important the role of entrepreneurial orientation is in improving the performance of MSMEs in Kudus Regency.